Kebijakan pendidikan di era society 5.0: tantangan dan peluang bagi pendidikan islam - Nafia, Jilan (Maliki Interdisciplinary Journal, 2026)
Currently, the Society 5.0 era brings significant impacts in the field of education, which requires policies that are adaptive to technological developments. Islamic education cannot rely solely on a well-designed curriculum, but also depends on how education policies are effectively implemented in the learning process within schools. Education policy serves as a direction and driving force in determining the quality of education, while its implementation plays a crucial role in ensuring that all educational components operate in harmony. Effective policies include well-structured planning, implementation, and evaluation processes that are continuous and sustainable. Islamic education must continuously adapt to technology-based policies, which offer great opportunities to improve educational quality. However, there are also various challenges, such as limited infrastructure, the readiness of human resources, and other related constraints. Therefore, the key to facing the era of Society 5.0 lies not only in formulating ideal education policies but also in ensuring their effective and integrative implementation while maintaining Islamic values. A collaboration between the government, educational institutions, and teachers is essential to ensure that education policies are implemented optimally and sustainably, enabling education to continuously develop in accordance with the needs of the times.